PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN ONLINE DI MA AS ADIYAH MATTIROWALIE KABUPATEN BONE - sulaeman sulaeman; jumarni jumarni; Muh Bachtiar Aziz; hasbullah hasbullah; Sabriadi HR Sabriadi HR (Atta'dib Jurnal Pendidikan Agama Islam, 2022)
This study aims to determine the effect of teacher pedagogic competence on the improvement of students' learning motivation in online learning and the motivation that most influences the online learning process. This research was conducted in Madrasah Aliyah As Adiyah Mattirowalie, Bone Regency. The population in this study were all stakeholders in the MA As Adiyah Mattirowalie educational institution, Bone Regency. The sampling technique used in this study is Nonprobability Sampling by selecting 10 samples needed in the study. Data were collected using questionnaire, observation and documentation instruments. Data were analyzed descriptively. The results showed that there was a positive influence of teacher pedagogic competence (variable X) on increasing students' learning motivation in online learning (variable Y) with a relationship between the two variables of 0.57.Keywords: teacher pedagogic, learning motivation